2001
DOI: 10.1046/j.1365-2273.2001.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Mohs micrographic surgery for facial skin cancer

Abstract: Although it is well established that conventional treatment modalities generally result in high cure rates for non-melanoma skin cancer, it has been demonstrated over recent decades that the highest overall cure rates are achieved using Mohs micrographic surgery. The key to Mohs surgery is the excision and control of complete peripheral and deep resection margins in one plane, allowing orientation, mapping and re-excision of microscopic tumour extension. These extensions can be followed without sacrificing ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 80 publications
4
64
0
4
Order By: Relevance
“…However, the need for MMS has been questioned because of many disadvantages related to this procedure. A single Mohs cycle, excluding the excision itself, takes approximately 45 min and, therefore, is extremely time consuming (29). The results of cost analysis in many studies showed that the mean costs of MMS were significantly high, mainly due to longer surgery time and high costs of pathological examination (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, the need for MMS has been questioned because of many disadvantages related to this procedure. A single Mohs cycle, excluding the excision itself, takes approximately 45 min and, therefore, is extremely time consuming (29). The results of cost analysis in many studies showed that the mean costs of MMS were significantly high, mainly due to longer surgery time and high costs of pathological examination (30).…”
Section: Discussionmentioning
confidence: 99%
“…Essa cirurgia é mais demorada do que outros métodos terapêuticos e requer material específico e cirurgião especializado na técnica, entretanto é custo-efetiva para o tratamento de grande parte dos tumores, uma vez que minimiza os riscos de recidivas e de mestástases. 1,2,4,6,14,[19][20][21][22] A duração da CMM está diretamente relacionada ao número de estádios cirúrgicos; prevê-los, portanto, vai auxiliar no preparo e orientação do paciente, da anestesia, da equipe e do agendamento cirúrgi-co. Também é importante predizer os CECs que necessitarão maior número de estádios cirúrgicos, pois eles são usualmente mais agressivos, têm maiores extensões subclínicas e necessitam de mais atenção durante a CMM.…”
Section: Discussionunclassified
“…Permite a remoção completa do tumor com máxima preservação do tecido sadio peritumoral. [1][2][3][4][5][6][7][8][9][10] Na CMM são examinadas 100% das margens do tecido removido através da análise histopatológica por congelação. Código de cores e mapa são confeccionados para determinar a exata localização de um possível tumor residual.…”
Section: Introductionunclassified
“…545,558,[564][565][566][567][568][569][570][571][572][573][574][575][576][577] In a seminal series of papers, Mohs reported 5-year cure rates for previously untreated SCCs of 95.7% for SCC of the trunk and extremities; 578 96.6% for the ear; 579 97.8% for facial, scalp and neck SCCs; 578 98.5% for eyelid SCCs; 580 and 98.8% for SCCs of the nose. 578 These rates translated to a pooled 5-year cure rate 97.4% for the 2133 SCCs at all sites (95% CI 96.2% to 98.3%; I 2 = 48%).…”
Section: Mohs Micrographic Surgerymentioning
confidence: 99%